2008
DOI: 10.1016/j.mrgentox.2008.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of a low mutant frequency after ionizing radiation-induced mutagenesis during spermatogenesis

Abstract: Humans are exposed to ionizing radiation (IR) under various circumstances, e.g. cosmic radiation, diagnostic X-rays and radiotherapy for cancer. It has been shown that IR can impair spermatogenesis and can cause mutations in germ cells. However, the mutagenic responses of germ cells exposed to IR at different stages of testicular maturation have not been examined by directly assessing the mutant frequency in defined spermatogenic cell types. This study was performed to address whether preadult exposure to IR c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…Many studies have indicated that germ cells and pluripotent cells use mechanisms to specifically limit the initial occurrence of spontaneous point mutations based on elevated levels of DNA repair pathways that ameliorate most potentially mutagenic DNA damage [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. These findings all support the disposable soma theory in that they suggest that a more stringent mechanism to maintain genetic integrity operating in germ cells or pluripotent cells leads to a lower mutational load than that found in somatic cells or differentiated cells, respectively.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Many studies have indicated that germ cells and pluripotent cells use mechanisms to specifically limit the initial occurrence of spontaneous point mutations based on elevated levels of DNA repair pathways that ameliorate most potentially mutagenic DNA damage [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. These findings all support the disposable soma theory in that they suggest that a more stringent mechanism to maintain genetic integrity operating in germ cells or pluripotent cells leads to a lower mutational load than that found in somatic cells or differentiated cells, respectively.…”
Section: Introductionmentioning
confidence: 74%
“…Several studies of DNA repair and cell death pathways have confirmed that these activities are elevated in germ cells relative to somatic cells [16][17][18][19][20][21][22][23][24]. Spontaneous DNA damage in spermatogenic cells is largely repaired through the base excision repair pathway or during replication by the mismatch repair system.…”
Section: Genetic Integrity In Germ Cellsmentioning
confidence: 99%
“…Mutation frequency declines during spermatogenic differentiation [Walter et al, 1998;Xu et al, 2008] suggesting that mechanisms have evolved to prevent germ cell transmission of genetic damage. Mutations induced by irradiation of A/B spermatogonia were shown to decline with cell differentiation, probably because of delayed apoptosis [Xu et al, 2008[Xu et al, , 2010. However, this protective process during spermatogenesis does not prevent all damaged cells from reaching the sperm stage, as shown by our studies and by others.…”
Section: Discussionmentioning
confidence: 99%
“…Primitive type A (collected from 6-day-old mice) and type A spermatogonia (collected from 8-day-old mice) have the highest spontaneous mutant frequencies, followed by type B spermatogonia, preleptotene spermatocytes, leptotene and zygotene spermatocytes, pachytene spermatocytes, round spermatids, and epididymal spermatozoa, all of which display a similarly low mutant frequency [1]. Ionizing radiation (IR) induces an increased mutant frequency that also declines as cells progress through spermatogenesis [3]. These data clearly show that one or more mechanisms reduce mutation load during spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It is unlikely, however, that DNA repair can mediate a decline in mutant frequency for fixed mutations. Apoptosis is another mechanism that may function in male germ cells to mediate a decline in mutant frequency during spermatogenesis by removing cells with a high mutant frequency [1,3]. However, little is known about the quantitative effects of apoptosis on mutant frequency, particularly in the germline.…”
Section: Introductionmentioning
confidence: 99%